Fungal biomolecules : sources, applications, and recent developments - Gupta, Vijai Kumar; Mach, Robert Ludwig; Sreenivasaprasad, S. (Chichester, West Sussex, UK : Wiley-Blackwell, 2015)
Fungi have an integral role to play in the development of the biotechnology and biomedical sectors. The fields of chemical engineering, Agri-food, Biochemical, pharmaceuticals, diagnostics and medical device development allemploy fungal products, with fungal biomolecules currently used in a wide range of applications, ranging from drug development to food technology and agricultural biotechnology. Understanding the biology of different fungi in diverse ecosystems, as well as their biotropic interactions with other microorganisms, animals and plants, is essential to underpin effective and innovative technological developments. Fungal Biomolecules is a keystone reference, integrating branches of fungal product research into a comprehensive volume of interdisciplinary research. As such, it:reflects state-of-the-art research and current emerging issues in fungal biology and biotechnology reviews the methods and experimental work used to investigate different aspects of fungal biomolecules provides examples of the diverse applications of fungal biomolecules in the areas of food, health and the environmentis edited by an experienced team, with contributions from international specialists This book is an invaluable resource for industry-based researchers, academic institutions and professionalsworking in the area of fungal biology and associated biomolecules for their applications in food technology, microbial and biochemical process, biotechnology, natural products, drug development and agriculture.
8.7 Properties and biological activities of peptaibiotics8.8 Conclusions; Acknowledgements; References; Section 3: Fungal secondary metabolites and synthesis; Chapter 9: Biosynthesis of silver nanoparticles by fungi; 9.1 Introduction; 9.2 Synthesis of silver NPs; 9.3 Physicochemical characterization of silver NPs; 9.4 Conclusions; References; Chapter 10: Fungal biomolecules as modulators of growth and pathogenesis; 10.1 Introduction; 10.2 Fungal biomolecules: Various potential applications and need for identification of novel bioactive molecules using innovative strategies
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Biofilms; Fungal enzymes -- Research; Aspergillus -- Research; SCIENCE -- Life Sciences -- Biology; SCIENCE -- Life Sciences -- Microbiology; Science; Electronic books